Cybercrime and islamic law: Revisiting the advantageous and hiatus horizon(s) - Sourodip Roy (Annals of Justice and Humanity, 2022)
Purpose: The purpose is to understand how Islamic law has been a positive dark effect in the field of law and provided much relief to the Muslim Community but it still consists of a negative light side to it, which is nowadays carried out throughout the virtual world. Islam means submission to the will of God (one who acknowledges the unity), believing in Alaa the founder of Islam Law is Prophet Mohammad before him the condition of the pre-Islamic period is known as gross ignorance (towards women), it’s almost a massacre. As Gandhi (2012), quoted Dr. Tahir Mahmood that “The story of the Shariat is indeed the pitiable story…unilaterally divorce their wives…Muslim Law in Indian mind… (Mahmood, as cited in Gandhi (2012)). Research Methodology: This short article would apply gender theory and Muslim law with an empirical methodology to deal with the Islamic period and Cyber Crime focusing on the complex web of intricate designs that are regulating gender harshly. Results: Therefore, the result will showcase the interrelated network of cyber criminology and Islamic Law provides the understanding of gender as the ‘other’ and restricts the fluidity of its existence. Limitations: The limitation of this article is the absence of data, which also appears as the possibility of future research by scholars. Contribution: This article will contribute to the domain of deciphering the reasons behind the heinous cyber crimes taking place based on Gendering the facets of political power flow.